Design of warp-knitted textile carriers for biofilm growth: towards scalable application in MBBR systems - Lenfeldová, Irena; Ryvolová, Martina; Kdýrová, Adéla (Discover applied sciences, 2025)
Textile-based carriers represent a promising alternative to conventional plastic media used in moving-bed biofilm reactors (MBBRs) for biological wastewater treatment. In this study, we developed and evaluated warp-knitted multifilament textile carriers intended to support biofilm growth, particularly under post-nitrification conditions. Four carrier variants were fabricated using combinations of polypropylene (PP) and polyester (PES) yarns to adjust material buoyancy (weight was in the range of 0.596 g to 0.612 g), dimension, 3D structures, and high surface availability for biofilm growth. The effective carrier area ranged from 4.6 × 10³ mm² to 5.3 × 10 3 mm 2 . Biofilm development was assessed through image analysis and oxygen uptake rate measurements. The positive effect of the holes on the water flowing through the carriers was not proven, but the long multifilament segment and the fibrous surface support bacterial growth. The warp-knitted spacer carriers developed in this study successfully supported the formation of active biofilms, as indicated by elevated oxygen consumption rates (OCR) reaching up to 8 mg O₂/L/h within six weeks of operation (OCR of 4–5 mg O₂/L/h was recorded for the plastic carrier). Only minor differences were observed between measurements taken at weeks 6 and 14, suggesting early stabilization of biofilm activity. Warp-knitted textile carriers show strong potential as biofilm-supporting media due to their structural flexibility, low weight, and scalability. Although compatibility with industrial systems has not yet been confirmed, the carriers were designed with this objective in mind and demonstrated rapid colonization and promising performance at the laboratory scale, suggesting their potential suitability for industrial applications. Graphical Abstract Highlights Microfiber carriers were developed and fabricated using warp knitting technology. Structural variability with holes and long multifilament segments allows scalability of the samples. Increasing the activated surface area and, thus, the oxygen uptake rate of textile carriers. 3D structure creates a supportive habitat and greatly accelerates biofilm growth.